Topological Entropy and Special α-Limit Points of Graph Maps - Taixiang Sun; Guangwang Su; Hailan Liang; Qiuli He (Discrete Dynamics in Nature and Society)
Let G a graph and f:G→G be a continuous map. Denote by h(f), R(f), and SA(f) the topological entropy, the set of recurrent points, and the set of special α-limit points of f, respectively. In this paper, we show that h(f)>0 if and only if SA(f)-R(f)≠∅.